Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
proof-pile / formal /lean /mathlib /algebra /cubic_discriminant.lean
Zhangir Azerbayev
squashed?
4365a98
raw
history blame
11.4 kB
/-
Copyright (c) 2022 David Kurniadi Angdinata. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: David Kurniadi Angdinata
-/
import field_theory.splitting_field
/-!
# Cubics and discriminants
This file defines cubic polynomials over a semiring and their discriminants over a splitting field.
## Main definitions
* `cubic`: the structure representing a cubic polynomial.
* `disc`: the discriminant of a cubic polynomial.
## Main statements
* `disc_ne_zero_iff_roots_nodup`: the cubic discriminant is not equal to zero if and only if
the cubic has no duplicate roots.
## References
* https://en.wikipedia.org/wiki/Cubic_equation
* https://en.wikipedia.org/wiki/Discriminant
## Tags
cubic, discriminant, polynomial, root
-/
noncomputable theory
/-- The structure representing a cubic polynomial. -/
@[ext] structure cubic (R : Type*) := (a b c d : R)
namespace cubic
open cubic polynomial
open_locale polynomial
variables {R S F K : Type*}
instance [inhabited R] : inhabited (cubic R) := ⟨⟨default, default, default, default⟩⟩
instance [has_zero R] : has_zero (cubic R) := ⟨⟨0, 0, 0, 0⟩⟩
section basic
variables {P : cubic R} [semiring R]
/-- Convert a cubic polynomial to a polynomial. -/
def to_poly (P : cubic R) : R[X] := C P.a * X ^ 3 + C P.b * X ^ 2 + C P.c * X + C P.d
/-! ### Coefficients -/
section coeff
private lemma coeffs :
(βˆ€ n > 3, P.to_poly.coeff n = 0) ∧ P.to_poly.coeff 3 = P.a ∧ P.to_poly.coeff 2 = P.b
∧ P.to_poly.coeff 1 = P.c ∧ P.to_poly.coeff 0 = P.d :=
begin
simp only [to_poly, coeff_add, coeff_C, coeff_C_mul_X, coeff_C_mul_X_pow],
norm_num,
intros n hn,
repeat { rw [if_neg] },
any_goals { linarith only [hn] },
repeat { rw [zero_add] }
end
@[simp] lemma coeff_gt_three (n : β„•) (hn : 3 < n) : P.to_poly.coeff n = 0 := coeffs.1 n hn
@[simp] lemma coeff_three : P.to_poly.coeff 3 = P.a := coeffs.2.1
@[simp] lemma coeff_two : P.to_poly.coeff 2 = P.b := coeffs.2.2.1
@[simp] lemma coeff_one : P.to_poly.coeff 1 = P.c := coeffs.2.2.2.1
@[simp] lemma coeff_zero : P.to_poly.coeff 0 = P.d := coeffs.2.2.2.2
lemma a_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.a = Q.a :=
by rw [← coeff_three, h, coeff_three]
lemma b_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.b = Q.b :=
by rw [← coeff_two, h, coeff_two]
lemma c_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.c = Q.c :=
by rw [← coeff_one, h, coeff_one]
lemma d_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.d = Q.d :=
by rw [← coeff_zero, h, coeff_zero]
@[simp] lemma to_poly_injective (P Q : cubic R) : P.to_poly = Q.to_poly ↔ P = Q :=
⟨λ h, cubic.ext _ _ (a_of_eq h) (b_of_eq h) (c_of_eq h) (d_of_eq h), congr_arg _⟩
@[simp] lemma of_a_eq_zero (ha : P.a = 0) : P.to_poly = C P.b * X ^ 2 + C P.c * X + C P.d :=
by rw [to_poly, C_eq_zero.mpr ha, zero_mul, zero_add]
@[simp] lemma of_a_b_eq_zero (ha : P.a = 0) (hb : P.b = 0) : P.to_poly = C P.c * X + C P.d :=
by rw [of_a_eq_zero ha, C_eq_zero.mpr hb, zero_mul, zero_add]
@[simp] lemma of_a_b_c_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) : P.to_poly = C P.d :=
by rw [of_a_b_eq_zero ha hb, C_eq_zero.mpr hc, zero_mul, zero_add]
@[simp] lemma of_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) (hd : P.d = 0) : P.to_poly = 0 :=
by rw [of_a_b_c_eq_zero ha hb hc, C_eq_zero.mpr hd]
@[simp] lemma zero : (0 : cubic R).to_poly = 0 := of_zero rfl rfl rfl rfl
@[simp] lemma eq_zero_iff : P.to_poly = 0 ↔ P = 0 := by rw [← zero, to_poly_injective]
lemma ne_zero (h0 : Β¬P.a = 0 ∨ Β¬P.b = 0 ∨ Β¬P.c = 0 ∨ Β¬P.d = 0) : P.to_poly β‰  0 :=
by { contrapose! h0, rw [eq_zero_iff.mp h0], exact ⟨rfl, rfl, rfl, rfl⟩ }
lemma ne_zero_of_a_ne_zero (ha : P.a β‰  0) : P.to_poly β‰  0 := (or_imp_distrib.mp ne_zero).1 ha
lemma ne_zero_of_b_ne_zero (hb : P.b β‰  0) : P.to_poly β‰  0 :=
(or_imp_distrib.mp (or_imp_distrib.mp ne_zero).2).1 hb
lemma ne_zero_of_c_ne_zero (hc : P.c β‰  0) : P.to_poly β‰  0 :=
(or_imp_distrib.mp (or_imp_distrib.mp (or_imp_distrib.mp ne_zero).2).2).1 hc
lemma ne_zero_of_d_ne_zero (hd : P.d β‰  0) : P.to_poly β‰  0 :=
(or_imp_distrib.mp (or_imp_distrib.mp (or_imp_distrib.mp ne_zero).2).2).2 hd
end coeff
/-! ### Degrees -/
section degree
/-- The equivalence between cubic polynomials and polynomials of degree at most three. -/
@[simps] def equiv : cubic R ≃ {p : R[X] // p.degree ≀ 3} :=
{ to_fun := λ P, ⟨P.to_poly, degree_cubic_le⟩,
inv_fun := λ f, ⟨coeff f 3, coeff f 2, coeff f 1, coeff f 0⟩,
left_inv := Ξ» P, by ext; simp only [subtype.coe_mk, coeffs],
right_inv := Ξ» f,
begin
ext (_ | _ | _ | _ | n); simp only [subtype.coe_mk, coeffs],
have h3 : 3 < n + 4 := by linarith only,
rw [coeff_gt_three _ h3,
(degree_le_iff_coeff_zero (f : R[X]) 3).mp f.2 _ $ with_bot.coe_lt_coe.mpr h3]
end }
lemma degree (ha : P.a β‰  0) : P.to_poly.degree = 3 := degree_cubic ha
lemma degree_of_a_eq_zero (ha : P.a = 0) (hb : P.b β‰  0) : P.to_poly.degree = 2 :=
by rw [of_a_eq_zero ha, degree_quadratic hb]
lemma degree_of_a_b_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c β‰  0) : P.to_poly.degree = 1 :=
by rw [of_a_b_eq_zero ha hb, degree_linear hc]
lemma degree_of_a_b_c_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) (hd : P.d β‰  0) :
P.to_poly.degree = 0 :=
by rw [of_a_b_c_eq_zero ha hb hc, degree_C hd]
lemma degree_of_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) (hd : P.d = 0) :
P.to_poly.degree = βŠ₯ :=
by rw [of_zero ha hb hc hd, degree_zero]
lemma leading_coeff (ha : P.a β‰  0) : P.to_poly.leading_coeff = P.a := leading_coeff_cubic ha
lemma leading_coeff_of_a_eq_zero (ha : P.a = 0) (hb : P.b β‰  0) : P.to_poly.leading_coeff = P.b :=
by rw [of_a_eq_zero ha, leading_coeff_quadratic hb]
lemma leading_coeff_of_a_b_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c β‰  0) :
P.to_poly.leading_coeff = P.c :=
by rw [of_a_b_eq_zero ha hb, leading_coeff_linear hc]
lemma leading_coeff_of_a_b_c_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) :
P.to_poly.leading_coeff = P.d :=
by rw [of_a_b_c_eq_zero ha hb hc, leading_coeff_C]
end degree
/-! ### Map across a homomorphism -/
section map
variables [semiring S] {Ο† : R β†’+* S}
/-- Map a cubic polynomial across a semiring homomorphism. -/
def map (Ο† : R β†’+* S) (P : cubic R) : cubic S := βŸ¨Ο† P.a, Ο† P.b, Ο† P.c, Ο† P.d⟩
lemma map_to_poly : (map Ο† P).to_poly = polynomial.map Ο† P.to_poly :=
by simp only [map, to_poly, map_C, map_X, polynomial.map_add, polynomial.map_mul,
polynomial.map_pow]
end map
end basic
section roots
open multiset
/-! ### Roots over an extension -/
section extension
variables {P : cubic R} [comm_ring R] [comm_ring S] {Ο† : R β†’+* S}
/-- The roots of a cubic polynomial. -/
def roots [is_domain R] (P : cubic R) : multiset R := P.to_poly.roots
lemma map_roots [is_domain S] : (map Ο† P).roots = (polynomial.map Ο† P.to_poly).roots :=
by rw [roots, map_to_poly]
theorem mem_roots_iff [is_domain R] (h0 : P.to_poly β‰  0) (x : R) :
x ∈ P.roots ↔ P.a * x ^ 3 + P.b * x ^ 2 + P.c * x + P.d = 0 :=
begin
rw [roots, mem_roots h0, is_root, to_poly],
simp only [eval_C, eval_X, eval_add, eval_mul, eval_pow]
end
theorem card_roots_le [is_domain R] [decidable_eq R] : P.roots.to_finset.card ≀ 3 :=
begin
apply (to_finset_card_le P.to_poly.roots).trans,
by_cases hP : P.to_poly = 0,
{ exact (card_roots' P.to_poly).trans (by { rw [hP, nat_degree_zero], exact zero_le 3 }) },
{ exact with_bot.coe_le_coe.1 ((card_roots hP).trans degree_cubic_le) }
end
end extension
variables {P : cubic F} [field F] [field K] {Ο† : F β†’+* K} {x y z : K}
/-! ### Roots over a splitting field -/
section split
theorem splits_iff_card_roots (ha : P.a β‰  0) : splits Ο† P.to_poly ↔ (map Ο† P).roots.card = 3 :=
begin
replace ha : (map Ο† P).a β‰  0 := (ring_hom.map_ne_zero Ο†).mpr ha,
nth_rewrite_lhs 0 [← ring_hom.id_comp Ο†],
rw [roots, ← splits_map_iff, ← map_to_poly, splits_iff_card_roots,
← ((degree_eq_iff_nat_degree_eq $ ne_zero_of_a_ne_zero ha).mp $ degree ha : _ = 3)]
end
theorem splits_iff_roots_eq_three (ha : P.a β‰  0) :
splits Ο† P.to_poly ↔ βˆƒ x y z : K, (map Ο† P).roots = {x, y, z} :=
by rw [splits_iff_card_roots ha, card_eq_three]
theorem eq_prod_three_roots (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
(map Ο† P).to_poly = C (Ο† P.a) * (X - C x) * (X - C y) * (X - C z) :=
begin
rw [map_to_poly, eq_prod_roots_of_splits $ (splits_iff_roots_eq_three ha).mpr $ exists.intro x $
exists.intro y $ exists.intro z h3, leading_coeff ha, ← map_roots, h3],
change C (Ο† P.a) * ((X - C x) ::β‚˜ (X - C y) ::β‚˜ {X - C z}).prod = _,
rw [prod_cons, prod_cons, prod_singleton, mul_assoc, mul_assoc]
end
theorem eq_sum_three_roots (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
map Ο† P = βŸ¨Ο† P.a, Ο† P.a * -(x + y + z), Ο† P.a * (x * y + x * z + y * z), Ο† P.a * -(x * y * z)⟩ :=
begin
apply_fun to_poly,
any_goals { exact Ξ» P Q, (to_poly_injective P Q).mp },
rw [eq_prod_three_roots ha h3, to_poly],
simp only [C_neg, C_add, C_mul],
ring1
end
theorem b_eq_three_roots (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
Ο† P.b = Ο† P.a * -(x + y + z) :=
by injection eq_sum_three_roots ha h3
theorem c_eq_three_roots (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
Ο† P.c = Ο† P.a * (x * y + x * z + y * z) :=
by injection eq_sum_three_roots ha h3
theorem d_eq_three_roots (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
Ο† P.d = Ο† P.a * -(x * y * z) :=
by injection eq_sum_three_roots ha h3
end split
/-! ### Discriminant over a splitting field -/
section discriminant
/-- The discriminant of a cubic polynomial. -/
def disc {R : Type*} [ring R] (P : cubic R) : R :=
P.b ^ 2 * P.c ^ 2 - 4 * P.a * P.c ^ 3 - 4 * P.b ^ 3 * P.d - 27 * P.a ^ 2 * P.d ^ 2
+ 18 * P.a * P.b * P.c * P.d
theorem disc_eq_prod_three_roots (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
Ο† P.disc = (Ο† P.a * Ο† P.a * (x - y) * (x - z) * (y - z)) ^ 2 :=
begin
simp only [disc, ring_hom.map_add, ring_hom.map_sub, ring_hom.map_mul, map_pow],
simp only [ring_hom.map_one, map_bit0, map_bit1],
rw [b_eq_three_roots ha h3, c_eq_three_roots ha h3, d_eq_three_roots ha h3],
ring1
end
theorem disc_ne_zero_iff_roots_ne (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
P.disc β‰  0 ↔ x β‰  y ∧ x β‰  z ∧ y β‰  z :=
begin
rw [← ring_hom.map_ne_zero Ο†, disc_eq_prod_three_roots ha h3, pow_two],
simp only [mul_ne_zero_iff, sub_ne_zero],
rw [ring_hom.map_ne_zero],
tautology
end
theorem disc_ne_zero_iff_roots_nodup (ha : P.a β‰  0) (h3 : (map Ο† P).roots = {x, y, z}) :
P.disc β‰  0 ↔ (map Ο† P).roots.nodup :=
begin
rw [disc_ne_zero_iff_roots_ne ha h3, h3],
change _ ↔ (x ::β‚˜ y ::β‚˜ {z}).nodup,
rw [nodup_cons, nodup_cons, mem_cons, mem_singleton, mem_singleton],
simp only [nodup_singleton],
tautology
end
theorem card_roots_of_disc_ne_zero [decidable_eq K] (ha : P.a β‰  0)
(h3 : (map Ο† P).roots = {x, y, z}) (hd : P.disc β‰  0) : (map Ο† P).roots.to_finset.card = 3 :=
begin
rw [to_finset_card_of_nodup $ (disc_ne_zero_iff_roots_nodup ha h3).mp hd,
← splits_iff_card_roots ha, splits_iff_roots_eq_three ha],
exact ⟨x, ⟨y, ⟨z, h3⟩⟩⟩
end
end discriminant
end roots
end cubic